The representation of motivational values In pictures containing the issue of motivation On pinterest website - Afianto, Tantra (2014)
This study investigates the representation of motivational values in pictures and the myths underlying the representations. The data are ten pictures containing the issue of motivation retrieved from Pinterest website. This study is a qualitative research framed in Barthes' orders of signification theory (1972). The theory is used to discover the representation of motivational values while the theory of motives by Murray (2009) becomes the foundation in revealing the myths from the representations. The result shows that there are three classifications of the representation of motivational values, namely the motivational values in general context, the motivational values in the context of health, and the motivational values in the context of sport. Moreover, of the three motivational values, there are five values: hard work, independence, total action, focus, and benefit of having opportunities. With regard to the myth, there are two motives, namely the motive of achievement and the motive of counteraction. In addition, there are three elaborations in the motive of achievement: (1) to overcome obstacles, (2) to accomplish something difficult, and (3) to master physical things. Furthermore, there are two elaborations in the motive of counteraction: to overcome weaknesses and to repress fear. This study suggests that besides motivational speech of particular people, any texts including pictures can be served as motivation. Key words: Representation, motives, motivational values, myths, Pinterest Kajian ini menginvestigasi representasi nilai-nilai motivasi dalam gambar-gambar dan mitos-mitos yang mendasari representasi tersebut. Datanya merupakan sepuluh gambar yang berisikan isu tentang motivasi yang diambil dari situs jaringan Pinterest. Kajian ini merupakan penilitian kualitatif yang terkerangka dalam teori tingkat pemaknaan oleh Barthes (1972). Teori tersebut digunakan untuk mengetahui representasi nilai-nilai motivasi sedangkan teori motif Murray (2009) menjadi dasar dalam mengungkap mitos-mitos dari representasi tersebut. Hasilnya menunjukan bahwa ada tiga klasifikasi representasi nilai-nilai motivasi, yaitu nilai-nilai motivasi dalam konteks umum, nilai-nilai motivasi dalam konteks kesehatan, dan nilai-nilai motivasi dalam konteks olahraga. Lebih jauhnya lagi, dari ketiga nilai-nilai motivasi tersebut, terdapat lima nilai: kerja keras, kemandirian, aksi total, fokus, dan manfaat memiliki kesempatan. Berkaitan dengan mitos, ada dua motif, yaitu motif prestasi dan motif mengatasi kelemahan. Ditambah lagi, ada tiga penjelasan dalam motif prestasi: (1) untuk mengatasi rintangan, (2) untuk menyeleasikan sesuatu yang sulit, dan (3) untuk menguasai hal-hal fisik. Selanjutnya, ada dua penjelasan mengenai motif mengatasi kelemahan: untuk mengatasi kelemahan dan untuk menekan rasa takut. Kajian ini menyarankan bahwa di samping pidato motivasi dari orang-orang tertentu, teks apapun termasuk gambar dapat berperan sebagai motivasi. Kata kunci: Representasi, motif, nilai-nilai motivasi, mitos, Pinterest